Hidden Mechanics of Exercise - Christopher M. Gillen (Harvard University Press, 2014)
At a local park on a warm summer eve ning, a teenager nails a three- pointer while her parents complete a long run. A skateboarder grinds across a rail while his grandmother crushes a backhand down the line. A shortstop nabs a line drive while her brother drills a penalty kick into the lower corner. These routine athletic movements demand power, coordination, and control. If we carefully watch athletes— even amateurs at the gym or on the playing fi elds— we see synchronized limbs, balanced bodies, and precise timing. We also observe occasional moments of clumsiness and frustration, highlighting the diffi culty of everyday athletic moves.